Math, asked by paulusmurmu88875, 11 months ago

4 গুন করাে-
( 4/3 xyz) X(1/3 yzx) X (-6xyz2)​

Answers

Answered by mysticd
2

 Given \:\Big( \frac{4}{3} xyz \Big)\times \Big( \frac{1}{3} yzx \Big) \times \Big( -6xyz^{2} \Big)

 = \frac{4}{3} \times \frac{1}{3} \times (-6) \times xyz \times xyz \times xyz^{2}

 = \frac{-8}{3} \times xxx \times yyy \times zzz^{2}

 = \frac{-8}{3} x^{1+1+1} \times y^{1+1+1} \times z^{1+1+2}

 = \frac{-8}{3} x^{3} \times y^{3} \times z^{4}

Therefore.,

 \red{\Big( \frac{4}{3} xyz \Big)\times \Big( \frac{1}{3} yzx \Big) \times \Big( -6xyz^{2} \Big)}

\green { = \frac{-8}{3} x^{3} \times y^{3} \times z^{4}}

•••♪

Similar questions